A Day Awake Attenuates Motor Learning-Induced Increases in Corticomotor Excitability - de Beukelaar, Toon T.; Van Soom, Jago; Huber, Reto; Wenderoth, Nicole (Frontiers in Human Neuroscience, 2016)
The “synaptic homeostasis hypothesis” proposes that the brain’s capacity to exhibit synaptic plasticity is reduced during the day but restores when sleeping. While this prediction has been confirmed for declarative memories, it is currently unknown whether it is also the case for motor memories. We quantified practice-induced changes in corticomotor excitability in response to repetitive motor sequence training as an indirect marker of synaptic plasticity in the primary motor cortex (M1). Subjects either practiced a motor sequence in the morning and a new motor sequence in the evening, i.e., after a 12 h period of wakefulness (wake group); or they practiced a sequence in the evening and a new sequence in the morning, i.e., after a 12 h period including sleep (sleep group). In both wake and sleep groups motor training improved movement performance irrespective of the time of day. Learning a new sequence in the morning triggered a clear increase in corticomotor excitability suggesting that motor training triggered synaptic adaptation in the M1 that was absent when a new sequence was learned in the evening. Thus, the magnitude of the practice-induced increase in corticomotor excitability was significantly influenced by time of day while the magnitude of motor performance improvements were not. These results suggest that the motor cortex’s potential to efficiently adapt to the environment by quickly adjusting synaptic strength in an activity-dependent manner is higher in the morning than in the evening.